THE EFFECT OF GUIDED INQUIRY LEARNING MODEL ASSISTED BY VIRTUAL LABORATORY TO STUDENT’S LEARNING ACHIEVEMENT IN TEMPERATURE AND HEAT TOPIC IN CLASS X OF SMA N 1 LANGSA ACADEMIC YEAR 2014/2015 - Mawarni Saputri; Motlan . (UNIVERSITAS NEGERI MEDAN, 2016)
ABSTRACT The aim of this research was to know the effect of guided inquiry learning model assisted by virtual laboratory to student’s learning achievement in temperature and heat topic in class X of SMA N 1 Langsa Academic year 2014/2015. The research method was quasi experimental. The population were all students of class X SMA N 1 Langsa Academic Year 2014/2015 that consist of 11 classes. Two classes selected by cluster random sampling as sample. One class as experiment class using guided inquiry learning model assisted by virtual laboratory and another class as control class using conventional learning. The instrument in this research were multiple choices and observational sheet. Multiple choices with 5 options and 20 questions were valid while observational sheet is used to measure the student’s activity during learning process. The results that were obtained: post test mean value of the experiment class was 78.70 and 63.54 was the mean value of the control class. Normality and homogeneity of the test result from the both samples was normal and homogenous. From the calculation of t test for post test data, obtained that tcount value was bigger than ttable value. Based on the observation that has been done by observers with using observational sheet obtained that student’s activity in experiment class is greater than control class. So, it can be concluded that there was the significant effect of guided inquiry learning model assisted by virtual laboratory to student’s learning achievement in temperature and heat topic in class X of SMA N 1 Langsa Academic year 2014/2015. Keywords: Guided inquiry learning model, virtual laboratory, student’s learning achievement, student’s activity.